186k views
1 vote
If
f(x) = 2x^2+5√((x-2)) complete the following statement:

f(6) = ____

2 Answers

0 votes

Answer: 82

Simply pug in 6 for
x


2(6)^2+5√((6-2)) \\72+5√(4) \\72+5(2)\\72+10=\\82

Hope this helps and have a great day!!!


Sofia

User Jepio
by
5.8k points
1 vote

For this case we have a function of the form
y = f (x).

Where:
f (x) = 2x ^ 2 + 5 \sqrt {x-2}

We must find the value of the function when x = 6, that is, f (6):

Then, replacing the value of "x"
f (6) = 2 (6) ^ 2 + 5 \sqrt {6-2}\\f (6) = 2 * 36 + 5 \sqrt {4}\\f (6) = 72 + 5 (2)\\f (6) = 72 + 10\\f (6) = 82

So,
f (6) = 82

ANswer:


f (6) = 82

User Imbryk
by
5.8k points